Recent and historical data show no evidence of Pacific bluefin tuna reproduction in the southern California Current system. - Heidi Dewar; Owyn E Snodgrass; Barbara A Muhling; Kurt M Schaefer (PLoS ONE, 2022)
Despite their broad distribution across the North Pacific Ocean, the only known spawning grounds for Pacific Bluefin Tuna (Thunnus orientalis) are around coastal Japan and the East China Sea. However, an increase in the prevalence of large bluefin tuna up to 10 years old in the California Current System during exceptionally warm ocean conditions has led to speculation that they may be spawning in this region. To investigate this possibility, we collected samples from 36 females (estimated 3-8 years old) between 2015 and 2019. Histological analyses revealed no signs of imminent, active, or recent spawning. Further examination of historical ichthyoplankton collections showed no records of larval bluefin tuna, but confirmed the presence of the larvae of other tuna species in waters > 24°C. Fishery-dependent records showed that bluefin tuna are rarely recorded in purse seine catches where surface temperatures exceed 23°C. Our study, therefore, provided no evidence of bluefin tuna reproduction in the CCS. However, more comprehensive sampling, in particular off southern Baja California, may be required to confirm the absence of spawning.